2022
DOI: 10.3390/ijms23179867
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Metabolism of the Natural Sweeteners Erythritol and Xylitol in Humans: A Dose-Ranging Study

Abstract: The natural sweeteners erythritol and xylitol might be helpful to reduce sugar consumption and therefore prevent obesity and diabetes. The aim of the present study was to determine the absorption and metabolization into erythronate of different concentrations of erythritol and xylitol. Seventeen healthy lean participants received intragastric solutions of 10, 25, or 50 g erythritol or 7, 17, or 35 g xylitol on three study days in a randomized order. The study was double blinded with respect to the doses admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
0
18
1
1
Order By: Relevance
“…The in vitro study by Maeng et al, 2019, examining the metabolism of erythritol in human and rat hepatocytes, reported that erythritol is stable and not metabolised. This is in contrast with the evidence emerging from the recent in vivo study by Bordier et al, 2022, from which metabolic transformation to erythronate, although limited, is shown. The Panel noted that the in vitro study used a much lower concentration of erythritol (41 uM) than that of the in vivo study.…”
Section: In Vitrocontrasting
confidence: 96%
See 3 more Smart Citations
“…The in vitro study by Maeng et al, 2019, examining the metabolism of erythritol in human and rat hepatocytes, reported that erythritol is stable and not metabolised. This is in contrast with the evidence emerging from the recent in vivo study by Bordier et al, 2022, from which metabolic transformation to erythronate, although limited, is shown. The Panel noted that the in vitro study used a much lower concentration of erythritol (41 uM) than that of the in vivo study.…”
Section: In Vitrocontrasting
confidence: 96%
“…The peak concentration in plasma was 240 μmol/L (29.3 mg/L) and the cumulative urinary excretion was 3.4 mmol, which corresponds to 41.5% of the dose ingested. Bordier et al (2022) performed a pharmacokinetic cross over study in 12 healthy volunteers receiving a bolus dose of 10, 25 or 50 g of erythritol dissolved in 300 mL tap water. Following ingestion, blood was taken and erythritol and erythronate were measured.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have revealed that xylitol is absorbed in the range of 49–95 % in the small intestine via passive diffusion and a slow absorption rate; however, xylitol was not found in plasma samples after two hours of ingestion. Xylitol can be excreted via the kidneys and fermented by beneficial bacteria [74] . On the other hand, citric acid can be absorbed in the gut or destroyed by bacteria and enzymes [75] .…”
Section: Discussionmentioning
confidence: 99%